A self-organizing approach: time synchronization for the HeNodeBs in heterogeneous network - Hasan, Mohammad Kamrul; Ismail, Ahmad Fadzil; Hassan Abdalla Hashim, Aisha; Mohd. Ramli, Huda Adibah; Hashim, Wahidah; Razzaque, Abdur; M.H., Khairolanuar (2015)
In Heterogeneous Network (HetNet) for LTE/LTE-A system femtocells (HeNodeBs) are designed and implemented to extend coverage and capacity. The arbitrary usage of HeNodeBs supported for indoor coverage is linked through a third-party internet backhaul to the HeNodeB managing server, and this is a segment of the operators end. To sustain HeNodeBs to the control function IEEE1588, master slave strategy is put in effect. Nevertheless, caused by the absence of internet or unfortunate connectivity for a prolonged period HeNodeBs undergoes synchronization difficulties that leads to frequency mismatch With this paper, a kind of self-organizing method is suggested for time synchronization in Heterogeneous Network, and that is standardized using IEEE1588 master slave method along with Precision Timing Protocol (PTP). The proposed approach is two way message transmission system, adopting the Least-squares Linear Regression Algorithm (LSRA) to reduce offsets as well as frequency misalignments (drift).